Multiaxial Testing of Materials Using a Stewart Platform: Case Study of the Nooru‐Mohamed Test. Issue 2 (4th April 2012) - Nierenberger, M.; Poncelet, M.; Pattofatto, S.; Hamouche, A.; Raka, B.; Virely, J.M.
<x xml:space="preserve">Abstract</x> A first application of a Stewart platform used as a multiaxial testing machine is presented. A specific case study is chosen, namely the so‐called Nooru‐Mohamed experiment, which is a tension‐shear test on a notched concrete specimen. The calibration, analysis of performances, and a validation test are investigated. The results confirm that the hexapod can be used to apply multiaxial loadings under small displacements, and allow also the measurement of the six components of forces and torques. Additional digital image correlation procedures are implemented at two scales of observation. Global measurements show the effect of the compliance of the device. Local measurements around the crack tip, necessary due to the small deformation of the specimen, give quantitative information about crack nucleation and propagation and will allow for future accurate numerical model validations.